The First Slovak-American Fraternal Organizations and Press - Michaela Bakay Zahorska (Communications - Scientific letters of the University of Zilina, 2012)
The aim of this work is to point out the characteristic features of the selected Slovak American fraternal organizations and Slovak press in the USA as the symbols of the raise of Slovak patriotism and the preservation of the Slovak cultural heritage .It provides the historical and political background of Slovak American immigration, settlement in the USA as well as the first political and fraternal activities that encouraged the Slovak nation to speak up for their rights and helped to awaken the Slovak interest in national issues, solidarity and a high sense of Slovak identity.